COMPETENCY OF PRIVATE EMPLOYEES IN IMMIGRATION WORK UNITS - Riri Ardyaningtyas; Guntur Widyanto (Polteknik Imigrasi, 2019)
Role of public relation as government media of publication can not be underestimated. The dissemination of information that spread rapidly by internet, government can take the advantage it as a tool for dissemination of information for services information or government’s programmes. A good information will come from employee who have a good competence in public relation. In other way, public relation activity should be supported by good infrastructure. In reality, many employee in office’s public relation do not have an enough competence. It has a strong influence for the quality of information. This research that measure people’s satisfication of public information that they have got and employee’s competence in public relations has a good result for people’s satisfication for public information. But, there are many lacks from employee’s competence in public relation. In the future, it’s important to make a public relations training or improve some infrastructure that supported for public relations activity.